Evaluation of Residual Stress in Selective Laser Melting of 316L Steel - Yadroitsava, Ina (2016)
Selective Laser Melting (SLM) has great potential in additive manufacturing methods because it allows producing full density complex parts with desired inner structure and surface morphology. Mechanical properties of SLM objects depend strongly on the material properties as well as strength of the connections between tracks and layers since all objects made by SLM are superposition of the single tracks and single layers. High temperature gradient as a result of the locally concentrated energy input can lead to residual stresses, crack formation and part deformations both during laser processing and after cutting objects from the substrate. X-ray diffraction method was used for investigation of residual stress in SLM samples from 316L steel fabricated by one-zone strategy with 50% overlap of the tracks. Samples had rectangular shape and different thickness: 50 µm (one layer), 0.2 mm (5 layers) and 1 mm (25 layers). All as-made samples attached to the substrate had the tensile stress. Normal residual stress along the scan direction was 1.2-1.7 times higher than perpendicular direction. In some areas residual stress was about and exceeded the yield strength of 316L wrought material.